Adipose Tissue - Szablewski, Leszek (IntechOpen, 2018)
Adipose tissue is a specialized connective tissue which, depending on type, plays different and significant roles in the human body: protects against environmental factors, stores lipids and triacylglycerol, synthesizes fatty acids and is involved in the process of thermogenesis. It is also a major secretory organ and highly active metabolic tissue. It secretes, for example, cholesterol, retinol, steroid hormones, prostaglandins and proteins known as "adipokines". Some of these molecules may be associated with pathologies such as obesity and insulin resistance. In humans, there are two main sites of adipose tissue accumulation: visceral and subcutaneous. Obesity is a worldwide health problem. This book also discusses a series of up-to-date topics about this pathology.